PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PERKEMBANGAN USAHA MIKRO (Studi pada Unit Pengelola Kegiatan Kecamatan Semparuk) - Safitri, Raya; Sumar'in (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
The Semparuk District Activity Management Unit (UPK) is an institution engaged in empowering rural communities, channeling financing to communities who need capital to run their businesses. The form of implementation of sharia financing is the principle of buying and selling based on a Murabahah contract and equipped with a Wakalah contract. The purpose of this study was to determine whether or not there is a positive or significant relationship between the effect of murabahah financing on the development of micro-enterprises. The theory used in this study is: 1) Murabahah Financing, 2) Micro Enterprises. This study uses a quantitative approach. Based on the results of simple linear regression analysis, it is known that there is a significant positive effect between murabahah financing on the development of micro-enterprises in the Semparuk District Activity Management Unit (UPK). This is shown by the results of the t test where the tcount value is 9,222 and the ttable value is 1.663. Therefore the value of tcount > ttable. Based on the results of the Coefficient of Determination (R²) test, the R Square value was 0.506. This shows that business development is affected by murabahah financing by 50.6% while the remaining 49,4% is influenced by other factors not discussed in this study. Thus it can be concluded that Ha is accepted and Ho is rejected.